(untitled) (Polis (Santiago), 2022)
This article’s main objective is to reflect on how and to what extent the pandemic affected and modified the forms of feminist activism in Chile? What impacts has the confinement had on the ways of organizing, the ability to convene and social pressure? What are the particularities of the Chilean case, given the pandemic ocurred in the midst of social revolt and the constituent process? What efforts have been made to stay active? Based on the results of the 8M 2021 Survey, the article reflects on the concretization of some key characteristics to understand and interpret contemporary Chilean feminisms, and through the results, it demonstrates the capacity for reinvention and feminist resistance to adapt to the context of pandemic-related confinement while continuing to activate as relevant political actors.